Two new species of small minnow mayfly (Ephemeroptera: Baetidae) from a mine-tailing dam disaster area in Minas Gerais, Brazil - de Lima, Cláudia R.t.; Massariol, Fabiana Criste; Cruz, Paulo Vilela; Hamada, Neusa (Zootaxa, 2022)
After the worst mine-tailing dam disaster which occurred in Minas Gerais state, Brazil, it was necessary to understand the extent of the biodiversity loss. Thus, based on legal obligations, a monitoring of the fauna and flora along the Rio Doce basin was developed. From this large study, surprisingly, two undescribed psammophilous mayfly species were collected. Given the environmental disaster, and the particular concern with species that inhabiting sandy bottom, the two new species may be already threatened. Considering the reported circumstances, our objective is to described the new species and carry out their extinction risk assessment following the IUCN protocol. Apobaetis irai sp. nov. can be distinguished by the size and shape of the setae in the distal middle area of the dorsal surface of the labrum, with 3 minutes, blunt spatulate setae and the shape of the labial palp; is likely to be threated, plausibly eligible, at least, as Vulnerable (VU) B2ab(iii)+D2. Rivudiva watu sp. nov., can be distinguished by the distal shape of glossae, absence of row of setae on ventral margin on the hind tibiae and hypopharynx without distomedial projection; given its distribution, it was not directly impacted by the disaster, however, there is not enough data to accurately estimate the extent of its occurrence (EOO) and area of occupancy (AOO), therefore, it may be eligible for Data Deficient (DD).